The social construction of integrity: a qualitative case study in Dutch Football. Issue 9 (2nd September 2022) - Loyens, Kim; Claringbould, Inge; Rossem, Leonie Heres - van; van Eekeren, Frank
Abstract: This study analyses how the social construction of integrity takes place within the context of football in the Netherlands. Combining a contextual approach to sports integrity with the analytic lens of sensemaking, this qualitative multi-method case study analyses – in one extreme case in Dutch youth amateur football – why and when the 'incident' was perceived as an 'integrity issue', and how the meaning of (the) integrity (issue) was socially constructed by (interactions between) stakeholders involved in the case. Our findings show why, when, and how moral norms and values are (not) debated and at stake, and that the social construction of sports integrity is intertwined with the institutional context and the role of secondary stakeholders. It provides insights that can help sports organizations to identify risks in their moral sports culture and to develop measures or policies to safeguard integrity in sports.